Birch Paper Company Revisited: An Exercise in Transfer Pricing. - Manes, Rene P. (The Accounting Review, 1970)
This exercise examines the possibility of using shadow prices to calculate transfer prices between divisions of the multi-division or conglomerate firm and of basing divisional profit statements on transfer prices derived in this way. In order to demonstrate the proposal, a well known Harvard Buisiness School case is modified in two ways so that two different linear programming solutions can be derived. Divisional income statements are then computed which indeed do exactly distribute the total profit of the firm each time, but these statements are found to have several unsatisfactory features for purposes of income determination. The exercise concludes by suggesting extensions for study and problem solving for the student.